Gene therapy during ex situ heart perfusion: a new frontier in cardiac regenerative medicine? - Vervoorn, Mats T.; Amelink, Jantijn J. G. J.; Ballan, Elisa M.; Doevendans, Pieter A.; Sluijter, Joost P. G.; Mishra, Mudit; Boink, Gerard J. J.; Bowles, Dawn E.; van der Kaaij, Niels P. (Frontiers in Cardiovascular Medicine, 2023)
Ex situ organ preservation by machine perfusion can improve preservation of organs for transplantation. Furthermore, machine perfusion opens up the possibilities for selective immunomodulation, creation of tolerance to ischemia-reperfusion injury and/or correction of a pathogenic genetic defect. The application of gene modifying therapies to treat heart diseases caused by pathogenic mutations during ex situ heart perfusion seems promising, especially given the limitations related to delivery of vectors that were encountered during clinical trials using in vivo cardiac gene therapy. By isolating the heart in a metabolically and immunologically favorable environment and preventing off-target effects and dilution, it is possible to directly control factors that enhance the success rate of cardiac gene therapy. A literature search of PubMed and Embase databases was performed to identify all relevant studies regarding gene therapy during ex situ heart perfusion, aiming to highlight important lessons learned and discuss future clinical prospects of this promising approach.